Green innovative economy remodeling based on economic complexity - Agnieszka Kowalska-Styczeń; Myroslava Bublyk; Vasyl Lytvyn (Journal of Open Innovation: Technology, Market and Complexity, 2023)
In this article, we propose a model of innovative economy remodeling, which aims to increase economic complexity by developing and investing in the green economy. We create this model for example of a transitional economy, which is the economy of Ukraine. For a comprehensive statistical analysis of the share of natural and energy resources in individual sectors of the economy, data on intermediate consumer costs from the first quadrant of the Input-Output table (Leontief model) were used for the first time. In this way, the most resource-intensive sectors of the economy and those that require investment in innovative technologies of green business are identified. The following sectors have the highest shares in the consumption of natural and water resources: C – Production; D – Electricity, gas, steam and air conditioning supply; E - Water supply; sewerage, waste management and remediation activities. In these sectors, first of all, implementing modern (knowledge-rich) green technologies should take place, which will reduce the consumption of natural and water resources. The proposed model can serve as a justification for the choice of investment directions in the remodeling of other economies in the transition period.